2003
DOI: 10.1007/s00134-003-1900-2
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 vs. ω-6 lipid emulsions exert differential influence on neutrophils in septic shock patients: impact on plasma fatty acids and lipid mediator generation

Abstract: omega-3 vs. omega-6 lipid emulsions differentially influence the plasma free fatty acid profile with impact on neutrophil functions. Lipid-based parenteral nutrition in septic patients may thus exert profound influence on sequelae and status of immunocompetence and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 64 publications
7
124
1
7
Order By: Relevance
“…However, evidence accumulated over the past few decades strongly suggests the lipid component of TPN as the most probable cause of PNALD. Both animal and human research during the past decade has implicated phytosterols and v-6 (n-6) fatty acids as the most likely components in the current lipid formulations as primary reasons for PNALD (8)(9)(10)(11)(12). In contrast, fish oil-based lipid emulsions (FOLEs) have been shown to be associated with full resolution of PNALD (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence accumulated over the past few decades strongly suggests the lipid component of TPN as the most probable cause of PNALD. Both animal and human research during the past decade has implicated phytosterols and v-6 (n-6) fatty acids as the most likely components in the current lipid formulations as primary reasons for PNALD (8)(9)(10)(11)(12). In contrast, fish oil-based lipid emulsions (FOLEs) have been shown to be associated with full resolution of PNALD (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fish oil-based lipid emulsions (FOLEs) have been shown to be associated with full resolution of PNALD (13)(14)(15)(16)(17)(18). The beneficial effects of FOLE have been attributed to the abundance of v-3 fatty acids, which, in contrast to v-6 fatty acids, have been shown to possess considerable anti-inflammatory properties (11,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, supplementation with fish oil is supposed to improve standard clinical therapy for chronic hyper-inflammatory diseases such as Crohn' disease [1,5] , rheumatoid arthritis [6] , cancer cachexia [7,8] , and as an adjunct therapeutic measure for trauma, injure, and sepsis [2,[9][10][11][12] . Although several studies have demonstrated the beneficial effects of omega-3 fatty acid supplementation on patient outcome or immune competence, randomized controlled clinical trials focusing on the use of parenteral fish oil are scarce [13][14][15][16][17] . The aim of this study was to assess whether parenteral supplementation of omega-3 fatty acid postoperatively improves the inflammatory and immunological function of colorectal cancer patients and their clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous administration, EPA and DHA promptly get incorporated into the cell membrane, compete with arachidonic acid (AA) in the cyclo-oxygenase and 5-lipoxygenase pathways, resulting in a reduced generation of diene prostanoids (e.g., PGE2, PGI2, and TXA2) and tetraene leukotrienes (e.g., LTB4), derived from AA in favor of the corresponding triene prostanoids (e.g., PGE3, PGI3, TXA3) and pentaene leukotriene (LTB5) derived from EPA [17].…”
Section: Discussionmentioning
confidence: 99%